2003
DOI: 10.1002/smi.950
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perceived social support and immune function

Abstract: Although a previous meta analysis showed some substantial relationships between social support and immune function, there is still no knowledge about the effects of social support on natural killer (NK) cell number. In this study we examined the direct relationships between peripheral lymphocyte subpopulations and several aspects of social support. We administered the Japanese version of the Stress and Coping Inventory (SCI) by Rahe (1994) to 98 male workers with a written informed consent. Blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…[ 64 65 ] Some studies have shown that social support leads to the improvement in health functions and even immunity performance. [ 66 67 68 ] Other studies on AIDS, indicators of body immunity, and on hemodialysis patients demonstrated a relationship between social support and these diseases in terms of their control and treatment. [ 69 70 71 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 64 65 ] Some studies have shown that social support leads to the improvement in health functions and even immunity performance. [ 66 67 68 ] Other studies on AIDS, indicators of body immunity, and on hemodialysis patients demonstrated a relationship between social support and these diseases in terms of their control and treatment. [ 69 70 71 ]…”
Section: Discussionmentioning
confidence: 99%
“…These results seem to hold across the life span, as studies found adolescents who reported low levels of social support also reported poorer health than those reporting higher levels of social support (Geckova, Van Dijk, Stewart, Groothoff, & Post, 2003), and older adults (60+) who reported insufficient social support reported poorer health than those satisfied with current support levels (White, Philogene, Fine, & Sinha, 2009). Researchers, such as Miyazaki et al (2003), found that a lack of perceived social support may indeed alter health and wellness on a cellular level. After controlling for age and smoking status, greater reported social support was associated with larger numbers of natural killer cells and a higher natural immunity.…”
Section: Social Support and Healthmentioning
confidence: 99%
“…The person’s survival depends on a network of peers, friends, family, and different formal and informal, real and virtual groups. Social support has positive health outcomes (e.g., Barth et al, 2010 ; Miyazaki et al, 2003 ) and significantly affects well-being (for meta-analysis, see Vera et al, 2020 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%